Planning literature education in schools based on literary ecology - Nori Anggraini; Ariyana, Ariyana (Universitas Ahmad Dahlan, 2024)
This study aims to describe how ecological values that emphasize environmental awareness can be incorporated into literature education in schools. This research is qualitative, using an ecocritical and collaborative approach. The results show that literature serves not only to entertain but also to educate and can be used to raise awareness among students by integrating ecological values into literature learning. The application of these values can be observed through the teaching of reading and writing literary works with themes about the current state of nature, the beauty of nature if undisturbed by human activity, how humans can protect the universe, and the consequences of environmental destruction for the survival of humanity and all it encompasses. This application can be implemented by adapting reading and writing materials to literary ecology within the Learning Objectives Flow, which will be developed in the Lesson Plan (RPP). It includes the use of learning resources aligned with the materials in the RPP, employing relevant learning media based on literature-based ecological reading and writing materials, and designing effective teaching methods suited to the material. By incorporating ecological values into literature education in schools, it is hoped that students will gain ecological awareness to contribute to saving the earth from further degradation.